The order of knowledge and robust action: How to deal with economic uncertainty? - Josef Falkinger (Kiel Institute for the World Economy (IfW), 2015)
Economic uncertainty has to do with the consequences of actions under different circumstances. This raises two questions: First, how sensitive are the outcomes of actions to variations in the environment? Second, how clearly can we distinguish between environments? Robustness comes at the price of targeting actions less narrowly to specific conditions, so we lose gains from specialization. Need for robustness comes from our limited knowledge. Rational dealing with uncertainty requires to accord the degree of specialization to the reliability of knowledge about the relevant circumstances. In practical terms, under such an approach acting under uncertainty is related to guidelines for strategic thinking: Focus on priorities on a broader scale; the most refined set of actions is not always the best one.
Keywords: D80; D81; D83; 330; limited knowledge; robustness; reliable information; risk and uncertainty; crisis tolerance